2020
DOI: 10.1038/s41467-020-17680-w
|View full text |Cite
|
Sign up to set email alerts
|

European polygenic risk score for prediction of breast cancer shows similar performance in Asian women

Abstract: Polygenic risk scores (PRS) have been shown to predict breast cancer risk in European women, but their utility in Asian women is unclear. Here we evaluate the best performing PRSs for European-ancestry women using data from 17,262 breast cancer cases and 17,695 controls of Asian ancestry from 13 case-control studies, and 10,255 Chinese women from a prospective cohort (413 incident breast cancers). Compared to women in the middle quintile of the risk distribution, women in the highest 1% of PRS distribution hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 34 publications
6
125
0
2
Order By: Relevance
“…Compared with patients in The Cancer Genome Atlas (TCGA) 10 , our patients were younger, presented at later stages and had higher proportions of ductal carcinoma and Her2 positivity (28.9% MyBrCa versus 19.3% TCGA when NAs are excluded; Supplementary Table 1 ). The MyBrCa tumour cohort includes Malaysians from a number of different ethnicities, primarily Chinese (89%), Malay (4.6%) and Indian (3.4%) (Supplementary Table 1 ), and is as a whole genetically similar to other East/Southeast Asian populations according to genotyping analysis 21 . A principal component analysis of our RNA-seq data did not reveal any significant differences across different ethnicities (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with patients in The Cancer Genome Atlas (TCGA) 10 , our patients were younger, presented at later stages and had higher proportions of ductal carcinoma and Her2 positivity (28.9% MyBrCa versus 19.3% TCGA when NAs are excluded; Supplementary Table 1 ). The MyBrCa tumour cohort includes Malaysians from a number of different ethnicities, primarily Chinese (89%), Malay (4.6%) and Indian (3.4%) (Supplementary Table 1 ), and is as a whole genetically similar to other East/Southeast Asian populations according to genotyping analysis 21 . A principal component analysis of our RNA-seq data did not reveal any significant differences across different ethnicities (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study used a genetic risk score based on 287 SNPs in a European population and found an AUC of about 0.63. They also found that this same genetic risk score is applicable to a Chinese population, where it had an AUC of about 0.61[29]. One genetic risk score to predict breast cancer risk is commercially available and has been validated in several large cohorts with over 100,000 women.…”
Section: Discussionmentioning
confidence: 99%
“…The PRSs are strati ed by setting cut offs at below 60th percentile for the low risk group, 60th to 95th percentile for intermediate risk group and above 95th percentile for the high risk group. In the Asian population, these cutoffs correspond to expected proportions of 51%, 41% and 8% for low, intermediate and high risk groups respectively [18]. The starting age for this strategy was chosen based on ndings that women with a high genetic risk for developing breast cancer may reach the equivalent 10-year risk to an average 50-year old woman at 35 years of age [18].…”
Section: Methodsmentioning
confidence: 99%
“…In the Asian population, these cutoffs correspond to expected proportions of 51%, 41% and 8% for low, intermediate and high risk groups respectively [18]. The starting age for this strategy was chosen based on ndings that women with a high genetic risk for developing breast cancer may reach the equivalent 10-year risk to an average 50-year old woman at 35 years of age [18]. There is no clear guideline on the ending age for mammogram.…”
Section: Methodsmentioning
confidence: 99%